2017
DOI: 10.1002/ange.201704492
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (±)‐Waihoensene

Abstract: The first total synthesis of waihoensene, a tetracyclic diterpene containing an angular triquinane and a six‐membered ring, with four contiguous quaternary carbon atoms, was achieved through the tandem cycloaddition reaction of an allenyl diazo substrate containing a six‐membered ring via trimethylenemethane (TMM) diyl intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…86 In the same work, Snyder and co-workers synthesized conidiogenones C (114) Waihoensene ( 10) is a tetracyclic diterpene; it was isolated from the New Zealand podocarp Podocarpus totara var waihoensis by Weavers and co-workers in 1997. 98 After the first racemic synthesis of 10 by Lee and co-workers in 2017, 99 the asymmetric synthesis of (+)-waihoensene (10) was reported by Yang's group 96 and Snyder's group 97 independently in 2020. A copper-catalyzed asymmetric conjugate reaction was the key synthetic step in each synthesis (Scheme 8).…”
Section: Conidiogenones and Conidiogenol (Snyder 2019) 82mentioning
confidence: 99%
“…86 In the same work, Snyder and co-workers synthesized conidiogenones C (114) Waihoensene ( 10) is a tetracyclic diterpene; it was isolated from the New Zealand podocarp Podocarpus totara var waihoensis by Weavers and co-workers in 1997. 98 After the first racemic synthesis of 10 by Lee and co-workers in 2017, 99 the asymmetric synthesis of (+)-waihoensene (10) was reported by Yang's group 96 and Snyder's group 97 independently in 2020. A copper-catalyzed asymmetric conjugate reaction was the key synthetic step in each synthesis (Scheme 8).…”
Section: Conidiogenones and Conidiogenol (Snyder 2019) 82mentioning
confidence: 99%
“…Due to the great difficulty in constructing such a tetracyclic framework with vicinal quaternary carbon centers, only one synthetic strategy toward waihoensene has been reported in 2017 using a tandem cycloaddition reaction of an allene substrate prepared in 12 steps as the key step. 17 Herein, based on the method we developed, starting from prop-2-yn-1-yl acetate 1g and 2h synthesized from the known reagent 8 in 6 steps, a facile access to a tricyclic skeleton was accomplished affording 5p in 40% yield and a dr ratio of 3.2/1 using hexauorobenzene as the solvent. 18 The relative conguration of 5p and its diastereoisomer 5q was conrmed by the X-ray structure analysis of their derivatives.…”
Section: Synthetic Applicationmentioning
confidence: 99%
“…In recent years, chemists have devoted much attention to addressing the synthetic challenges posed by terpenes, such as 1-3 (Scheme 1), which possess a modicum of traditionally reactive functional groups. [1][2][3][4] Indeed, efforts with such molecules have suggested that since functional groups are typically required to forge C-C bonds, they should be chosen strategically and used for multiple purposes to limit step counts since they oen are target superuous. 5 In addition, when multiple quaternary centers are present, 6 they should be used as an essential part of retrosynthetic planning, focused on the question of how the presence of one might assist in the formation of others.…”
Section: Introductionmentioning
confidence: 99%